2022
DOI: 10.1021/acsomega.2c05001
|View full text |Cite
|
Sign up to set email alerts
|

The Hole Sealing Technology of Solid–Liquid Materials with Three Pluggings and Two Injections for Gas Extraction Hole in the Coal Mine

Abstract: The sealing quality of the gas extraction holes determines the extracted gas concentration. Based on this, the paper reveals the basic principle of hole sealing by analyzing the gas leakage mechanism of the borehole. The hole sealing technology of solid–liquid materials with three pluggings and two injections for the gas extraction hole is proposed, and the hole sealing device and material are developed. Through testing the granularity distribution of the solid material, as well as the surface tension and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This results in a sharp increase in the permeability coefficient of the coal body in the drilling range, forming an air leakage channel from the drill hole. Under the effect of negative pressure, a large amount of outside air can flow into the borehole through the air leakage channel, which greatly decreases the gas concentration during late-stage borehole extraction, reduces the negative pressure of extraction, and causes a rapid decline in the amount of pure gas extracted. Scholars have conducted substantial engineering research on drill hole sealing materials to improve the concentration and efficiency of gas extraction. Common sealing materials are clay-, polyurethane-, and cement-based materials. Clay is inexpensive and includes a wide range of materials; however, achieving efficient borehole degassing with the clay sealing method, as a manual operation, is time-consuming and labor-intensive .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in a sharp increase in the permeability coefficient of the coal body in the drilling range, forming an air leakage channel from the drill hole. Under the effect of negative pressure, a large amount of outside air can flow into the borehole through the air leakage channel, which greatly decreases the gas concentration during late-stage borehole extraction, reduces the negative pressure of extraction, and causes a rapid decline in the amount of pure gas extracted. Scholars have conducted substantial engineering research on drill hole sealing materials to improve the concentration and efficiency of gas extraction. Common sealing materials are clay-, polyurethane-, and cement-based materials. Clay is inexpensive and includes a wide range of materials; however, achieving efficient borehole degassing with the clay sealing method, as a manual operation, is time-consuming and labor-intensive .…”
Section: Introductionmentioning
confidence: 99%
“… 9 11 Scholars have conducted substantial engineering research on drill hole sealing materials to improve the concentration and efficiency of gas extraction. 12 14 Common sealing materials are clay-, polyurethane-, and cement-based materials. Clay is inexpensive and includes a wide range of materials; however, achieving efficient borehole degassing with the clay sealing method, as a manual operation, is time-consuming and labor-intensive.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the quality of hole sealing, scholars have conducted extensive research on sealing material and technology. Yu et al 16 put forward the solid–liquid sealing technology of “three plugging and two injection” and developed the sealing device and materials. Xiong et al 17 tested three different sealing technologies, namely, bagged polyurethane sealing, self-expanding sealing device, and new-type expansive cement sealing.…”
Section: Introductionmentioning
confidence: 99%
“…Since the coal reservoir is porous and there exist massive pores and cracks inside the coal seam, both the heat carrier such as nitrogen or water vapor and the pyrolysis products such as the gaseous tar, methane, carbon monoxide, carbon dioxide and hydrogen would diffuse through the pores and cracks to the production well [3]. Some research has focused on coal seam gas [4][5][6][7]. For example, Wang et al [4,5] studied the influence of negative pressure on the leakage during the extraction of coalbed methane and found that the active support method using delayed expansion material can effectively reduce the formation of crack micropores and reduce stress concentration.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al [4,5] studied the influence of negative pressure on the leakage during the extraction of coalbed methane and found that the active support method using delayed expansion material can effectively reduce the formation of crack micropores and reduce stress concentration. The technology of sealing holes with three plugging and two filling solid and liquid materials is put forward to realize continuous high-concentration gas extraction [6]. Zhu et al [7] developed a simulation model to evaluate the effect of penetrating fractures on lateral water flow and to study the effect of permeability on gas storage and production in coal seams.…”
Section: Introductionmentioning
confidence: 99%